Effect of Unilateral Acoustic Trauma on Neuronal Firing Activity in the Inferior Colliculus of Mice - Hsiao, Chun-Jen; Galazyuk, Alexander V. (Frontiers in Synaptic Neuroscience, 2021)
Hyperactivity caused by sound exposure often led to development of hyperacusis and/or tinnitus. Hyperactivity in laboratory animals is typically induced by unilateral sound exposure to preserve one ear for further testing of hearing performance. Most ascending fibers in the auditory system cross into the superior olivary complex and then ascends through the contralateral side. Therefore, unilateral exposure should be expected to mostly affect the contralateral side above the auditory brain stem. On the other hand, it is well known that a significant number of neurons have crossing fibers at every level of the auditory pathway, which may help spreading the effect of unilateral exposure on the ipsilateral side. Here we demonstrate that unilateral sound exposure causes development of hyperactivity in both the contra and ipsilateral inferior colliculus in mice. We found that both the spontaneous firing rate and bursting activity were increased significantly compared to unexposed mice. The neurons with characteristic frequencies at or above the center frequency of exposure showed the greatest increase. Surprisingly, this increase was more pronounced in the ipsilateral inferior colliculus. This study highlights the importance for the future studies utilizing unilateral sound exposure, pay close attention to the side of recording.